High Gene Transfer by the Osmotic Polysorbitol-Mediated Transporter through the Selective Caveolae Endocytic Pathway - Luu, Quynh-Phuong; Shin, Ji-Young; Kim, You-Kyoung; Islam, Mohammad Ariful; Kang, Sang-Kee; Cho, Myung-Haing; Choi, Yun-Jaie; Cho, Chong-Su (Molecular pharmaceutics, 2012)
Cationic polymers have been the subject of intense research as nonviral gene delivery systems due to several advantages in comparison with viral vectors. However, the nonsimultaneous combination of high transfection efficiency and low cytotoxicity of nonviral vectors for gene delivery has long been an issue for scientists looking into ways to deliver genes into cells. Toward this goal, we designed, synthesized, and evaluated a safe and accelerated gene transfer system through polysorbitol-mediated transporter (PSMT) based on sorbitol diacrylate (SDA) and low molecular weight polyethylenimine (LMW PEI). The PSMT formed stable complexes with plasmid DNA in serum. The nano sizes and spherical shapes of PSMT/DNA complexes are not toxic, even at a high concentration of PSMT. The higher transfection efficiency of PSMT compared to PEI 25K was observed both in vitro, despite the existence of many hydroxyl groups, and in vivo. These improvements presumably stem from the osmotic property of polysorbitol and endosomal buffer capacity of PEI in PSMT. Most importantly, we confirmed that the selective cavaeolae endocytic pathway played a role in high transfection efficiency by osmotic PSMT-mediated gene delivery. We propose that PSMT is a promising nonviral carrier for the effective gene delivery to cancer cells via synergistic effects derived from rapid cellular uptake through the caveolae endocytic pathway and a high endosomal buffering capacity.